A novel speed control strategy for 3-phase induction motor drives with star-connected under single-phase open-circuit fault using modified RFOC strategy. (June 2022) - Tabasian, Rahemeh; Ghanbari, Mahmood; Esmaeli, Abdolreza; Jannati, Mohammad
Abstract: In this research, a novel control method is proposed for 3-Phase Induction Motor (3-PIM) drives with star-connected under Single-Phase Open-Circuit (SPOC) fault using modified Rotor Field-Oriented Control (RFOC) strategy. The standard RFOC strategy is designed based on the d − q model of 3-PIM during normal mode. This strategy cannot be applied for a 3-PIM under SPOC fault as the model of a healthy 3-PIM is different from the model of a faulty 3-PIM. The use of standard RFOC strategy for Vector Control (VC) of a 3-PIM under SPOC fault increases the electromagnetic torque ripples during this fault. To overcome this problem, two unbalanced rotational transformations are used. A Current Transformation Matrix (CTM) is obtained based on the concept of maintaining value of Magnetic Motive Force (MMF) of the faulted machine like the healthy machine. Then, a Voltage Transformation Matrix (VTM) is introduced by using the presented CTM and according to the Single-Phase Induction Motor (SPIM) model. Based on the results, faulted machine RFOC equations were obtained similar to the healthy machine RFOC equations by using the CTM and VTM. The proposed technique was verified by simulations and experiments. Results indicated that the performances of the faulted machine under the proposed RFOC strategy are better than standard control techniques. Highlights: A modified RFOC strategy for star-connected 3-PIMs under open phase fault has been presented. The overall performances of the basic RFOC system during open-phase fault have been improved. A simple and accurate FTC system in comparison with other previous FTC schemes has been proposed. The introduced control technique can be used to control SPIM drive systems.